Customer-Brand Relationship What the Universities Should Know - Sharizal, Hashim; Norjaya, Mohd Yasin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The understanding of how customers establish their relationship with brands has attracted much attention over the years and has become a topic of interest in social and economic discussions. The concept of Customer Brand Relationship has been considered an important concept due to its intangibility and complex in nature. Although this seems to be the case, there has been limited attempts to examine its formation and development as well as its application in the service setting particularly in the context of university services. For instance, there is still very few books on Customer Brand Relationship that really emphasized on its origin and other important issues such as its context, theories, antecedents and consequence pertaining to its formation and development. Given this limitation, and the variety of issues pertaining to customer brand relationship quality and its antecedents and consequences that have yet to be fully addressed, there is therefore, a need for further works in this field of study.